Approximation Through Common and Differential Modes for Twist Wire Pair Crosstalk Model - Sun, Yaxiu; Jiang, Qinghui; Yu, Wenhua; Zhuo, Qingkun; Li, Qian (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, an advanced approximation method is presented, which separates the twist wire pairs into common and differential modes using the multi-conductor transmission line model. The simulation storage and time cost has been significantly reduced and its accuracy is better than traditional approximation methods. Analyses of dealing with the impedance and admittance and the separation procedure of common and differential modes are presented. In addition, the load dealing methods for terminal and source has also been specified in this paper. Numerical experiments validate the accuracy and listed the storage efficiency and time cost reduction of the proposed method.